Does on-the-job training help graduates find a job? Evidence from an Italian region. Issue 3 (6th February 2019) - Ghirelli, Corinna; Havari, Enkelejda; Santangelo, Giulia; Scettri, Marta
Abstract : Purpose: The purpose of this paper is to evaluate a recent training programme for graduates, implemented in Italy and entitled Work Experience Laureati and Laureate, i.e. Work Experience for Graduates. The aim of the programme was to increase the career prospects of unemployed graduates in the region of Umbria. Design/methodology/approach: The authors rely on administrative data and matching methods to evaluate the effectiveness of the intervention in terms of employability of participants. Findings: The results show that participants are more likely to be employed and to sign an apprenticeship contract within the region boundaries. The authors also find substantial differences in employability and type of contract by gender, with men having a higher probability of finding a job (permanent contract and apprenticeship). The authors show that this may be explained by the different choices in terms of field of study, with males being more prone to enrol in scientific areas and females in the humanities. Research limitations/implications: It is an intervention implemented in one Italian region. Originality/value: This is one of the few studies that analyses the effectiveness of active labour market policies targeting unemployed graduates, especially in the Italian context. The authors rely on different administrative data sources that allow them to evaluate the effectiveness of the programme.